2007
DOI: 10.1038/sj.gene.6364447
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes that influence sex hormone-dependent disease phenotypes in mouse lupus

Abstract: Ninety percent of systemic lupus erythematosus patients are female, and gender differences in lupus susceptibility are also observed in (New Zealand Black  New Zealand White)F1 (BWF1) lupus-prone mice. We followed orchiectomized, intact male and female BWF1 mice for lupus-like disease for 1 year. A comparative gene expression analysis was then used to identify candidate genes potentially responsible for gender-dependent differences in lupus susceptibility. Seven genes encoded on the sex chromosomes and 77 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 37 publications
(37 reference statements)
1
33
0
Order By: Relevance
“…The role of estrogen, which influences both humoral and cellular immunity, has been widely studied and particularly in the NZB/W F1 mouse model of spontaneous SLE [47]. Female NZB/W F1 females die of SLE more rapidly than do males [6, 48].…”
Section: Discussionmentioning
confidence: 99%
“…The role of estrogen, which influences both humoral and cellular immunity, has been widely studied and particularly in the NZB/W F1 mouse model of spontaneous SLE [47]. Female NZB/W F1 females die of SLE more rapidly than do males [6, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Male (NZB × NZW)F 1 mice were orchiectomized at 3 months of age as described (35). After orchiectomy, pellets (Innovative Research of America, Sarasota, FL, USA) releasing E2, DHT, or placebo (P) for up to 3 weeks were inserted subcutaneously with a 10-gauge needle.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have suggested that gender differences in lupus susceptibility are mediated by sex hormones, consistent with the fact that 90% of SLE sufferers are female [5456]. For example, there is an increased risk of developing SLE in postmenopausal women who received estrogen hormone replacement therapy [57].…”
Section: Influence Of Estrogen In Cytokine Networkmentioning
confidence: 96%